The characteristics and formation mechanisms of emissions from thermal decomposition of 3D printer polymer filaments - Ding, Shirun (2020)
Ultrafine particles (UFP) and volatile organic compounds (VOC) emitted from fused deposition modelling (FDM) 3D printing have received widespread attention. Here, we characterize the formation mechanisms of emissions from polymer filaments commonly used in FDM 3D printing. The temporal relationship between the amount and species of total VOC (TVOC) at any desired operating thermal condition is obtained through a combination of evolved gas analysis (EGA) and thermogravimetric analysis (TGA) to capture physicochemical reactions, in which the furnace of EGA or TGA closely resembles the heating process of the nozzle in the FDM 3D printer. It is generally observed that emissions initiate at the start of the glass transition process and peak during liquefaction for filaments. Initial increment in emissions during liquefaction and the relatively constant decomposition of products in the liquid phase are two main TVOC formation mechanisms. More importantly, low heating rate has the potential to restrain the formation of carcinogenic monomer, styrene, from ABS. A TVOC measurement method based on weight loss is further proposed and found that TVOC mass yield was 0.03%, 0.21% and 2.14% for PLA, ABS, and PVA, respectively, at 220 °C. Among TVOC, UFP mass accounts for 1% to 5% of TVOC mass depending on the type of filaments used. Also, for the first time, emission of UFP from the nozzle is directly observed through laser imaging.